Pathogenesis of encephalitis induced in newborn mice by virulent and avirulent strains of Sindbis virus. - Sherman, L A (1990)
Strains of Sindbis virus differ in their virulence for mice of different ages; this variation is related in large part to variations in the amino acid compositions of E1 and E2, the surface glycoproteins. The comparative pathogenesis of Sindbis virus strains which are virulent or avirulent for newborn mice has not been previously examined. We have studied the diseases caused by a virulent wild-type strain, AR339, and two less virulent laboratory strains, Toto1101 and HRSP (HR small plaque). After peripheral inoculation of 1,000 PFU, AR339 causes 100% mortality within 5 days (50% lethal dose [LD50] = 3 PFU) while Toto1101 causes 70% mortality (LD50 = 10(2.4) PFU) and HRSP causes 50 to 60% mortality (LD50 = 10(5.1) PFU) with most deaths occurring 7 to 11 days after infection. However, after intracerebral inoculation of 1,000 PFU, Toto1101 is virulent (100% mortality within 5 days; LD50 = 4 PFU) while HRSP is not (75% mortality; LD50 = 10(4.2) PFU). After intracerebral inoculation, all three strains initiate new virus formation within 4 h, but HRSP reaches a plateau of 10(6) PFU/g of brain while Toto1101 and AR339 replicate to a level of 10(8) to 10(9) PFU/g of brain within 24 h. Interferon induction parallels virus growth. Mice infected with HRSP develop persistent central nervous system infection (10(6) PFU/g of brain) until the initiation of a virus-specific immune response 7 to 8 days after infection when virus clearance begins. The distribution of virus in the brains of mice was similar, but the virus was more abundant in the case of AR339. HRSP continued to spread until day 9. Clearance from the brain was complete by day 17. We conclude that the decreased virulence of HRSP is due to an intrinsic decreased ability of this strain of Sindbis virus to grow in neural cells of the mouse. We also conclude that CD-1 mice do not respond to the antigens of Sindbis virus until approximately 1 week of age. This lack of response does not lead to tolerance and persistent infection but rather to late virus clearance whenever the immune response is initiated.